2014
DOI: 10.3349/ymj.2014.55.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Positive Maternal C-Reactive Protein Predicts Neonatal Sepsis

Abstract: PurposeTo evaluate the diagnostic performance of maternal inflammatory marker: C-reactive protein (CRP) in predicting early onset neonatal sepsis (that occurring within 72 hours after birth).Materials and Methods126 low birth weight newborns (gestation 32±3.2 wk, birth weight 1887±623 g) and their mothers were included. Neonates were divided into sepsis group (n=51) including both proven (positive blood culture) and suspected (negative blood culture but with more than 3 abnormal clinical signs), and controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…The importance of CRP levels in serum for the diagnosis of funisitis / chorioamnionitis (27)(28)(29)(30), for the determination of neonatal sepsis (31) and the association between neonatal infection and funisitis / chorioamnionitis are discussed in many works of various authors (32)(33). For example, van de Laar made a very important review of scientific works.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of CRP levels in serum for the diagnosis of funisitis / chorioamnionitis (27)(28)(29)(30), for the determination of neonatal sepsis (31) and the association between neonatal infection and funisitis / chorioamnionitis are discussed in many works of various authors (32)(33). For example, van de Laar made a very important review of scientific works.…”
Section: Discussionmentioning
confidence: 99%
“…19 These elevations in CRP have been found to remain consistently high from the earliest stages of pregnancy through to childbirth. 19e21 However, a higher than usual inflammatory response in pregnant women, as measured by CRP, also has been related to adverse pregnancy outcomes, including preeclampsia, neonatal sepsis, 22 preterm delivery, 23,24 and intrauterine growth restriction. 6,23,25 The present data did not reflect any differences in birth outcomes, as measured by preterm delivery and low birth weight, associated with increased CRP levels in unadjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein (CRP) is an acute inflammatory phase protein produced in the liver, currently believed to be a reliable indicator of inflammation and tissue damage, as it is elevated in cases of infection, inflammatory response, damage, and necrosis of the tissue [16]. Among its actions are platelet activation, chemotaxis acceleration, and enhancement of cell-mediated immunity by promoting phagocytosis [17].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…In 2013, a study conducted at the Department of Pediatrics at Yonsei University of Medicine showed that high levels of CRP in the mother may indicate a risk of infection of the newborn and that these values would be related to the severity of the disease presented by these babies [16].…”
Section: C-reactive Proteinmentioning
confidence: 99%